Influence of Livelihood Capitals on Landscape Service Cognition and Behavioral Intentions in Rural Heritage Sites - Shiying Li; Yaqi Cheng; Jiayu Cai; Xuewei Zhang (Land)
Farmers’ livelihoods are critical for global sustainable development and the conservation and transmission of rural heritage. However, neglecting farmers’ livelihoods increases the risks to living heritage conservation. Therefore, it is essential to explore the impact of livelihood capital on farmers’ landscape services cognition and their behavioral intentions. Based on the Sustainable Livelihoods Approach, this study examines the rural areas of Mulanbei irrigation district, which was recognized as a World Heritage Irrigation Structure in 2014, and uses a structural equation model to investigate the relationships between farmers’ livelihood capital, landscape services cognition and behavioral intentions. The study’s key findings include the following: (1) The levels of human capital (0.541), social capital (0.671), and cultural capital (0.645) are relatively high, while the levels of natural, physical, and financial capital are comparatively low. (2) There are significant differences in landscape service cognition and behavioral intentions among farmers of different livelihood strategies, with diversified livelihood farmers demonstrating the highest levels of both cognition and intentions, while subsidy-dependent farmers show the lowest levels. (3) Natural, cultural and financial capital play a crucial role in influencing farmers’ landscape services cognition and their behavioral intentions. Landscape service cognition mediates the relationship between livelihood capital and behavioral intentions. (4) To increase farmers’ willingness to protect and promote rural heritage, efforts should focus on enhancing natural, physical, and financial capital while fostering cultural capital to promote advocacy.